2016
DOI: 10.1002/adma.201506238
|View full text |Cite
|
Sign up to set email alerts
|

Color Depth Modulation and Resolution in Phase‐Change Material Nanodisplays

Abstract: The demonstration of non‐volatile color‐depth modulation in novel phase change nanodisplays allowing for continuous “grayscale” images with ultrahigh resolution and low dimensionality is described. These results hold promise for a new generation of bistable, ultrahigh‐resolution, and flexible display technologies, while allowing for other potential applications in nanophotonics and optoelectronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
125
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 31 publications
1
125
0
Order By: Relevance
“…[6] Exploiting both optical and electrical properties of phase-change materials simultaneously, and the possibility of modulating optical effects using electrical excitations, has only very recently opened up new application fields, such as low-power, nonvolatile, phase-change nano displays. [7][8][9] A deeper understanding of the relationship between the optical and electrical properties of phase-change materials, such as GST, is now urgently required to spur the development of new optoelectronic applications.…”
Section: Doi: 101002/aelm201700079mentioning
confidence: 99%
“…[6] Exploiting both optical and electrical properties of phase-change materials simultaneously, and the possibility of modulating optical effects using electrical excitations, has only very recently opened up new application fields, such as low-power, nonvolatile, phase-change nano displays. [7][8][9] A deeper understanding of the relationship between the optical and electrical properties of phase-change materials, such as GST, is now urgently required to spur the development of new optoelectronic applications.…”
Section: Doi: 101002/aelm201700079mentioning
confidence: 99%
“…Only two colours can be tuned via the full crystallization of the few-nanometres-thick GST layer without the contribution provided by changing the thickness of indium tin oxide (ITO) beneath the GST. Previous studies tend to use single phase change material (PCM) as a highly absorbing dielectric layer to realize colour depth modulation, for example, Ag 3 In 4 Sb 76 Te 17 (AIST)9 and two ultrathin GST films10. However, the method based on two ultrathin GST films needs a barrier layer to avoid interdiffusion, which will adversely interfere with the amorphization during actual device operation10 and is unstable because it need accurate thickness control.…”
mentioning
confidence: 99%
“…Furthermore, PCMs can also be used to produce nanodisplays . It is first reported that an optoelectronic framework based on PCMs is capable of displaying on both rigid and flexible films .…”
Section: Tuning Via Phase Transitionsmentioning
confidence: 99%
“…A conducting atomic force microscope (CAFM) is used to construct the image, where the contrast comes from the different states of each pixel, as shown in Figure f. It is later reported by the same group that instead of GST, another phase‐change alloy Ag 3 In 4 Sb 76 Te 17 (AIST) can be used to make a colorful rendering with improved depth modulation capability …”
Section: Tuning Via Phase Transitionsmentioning
confidence: 99%